2015
DOI: 10.1017/s0014479714000593
|View full text |Cite
|
Sign up to set email alerts
|

ECOPHYSIOLOGICAL TRAITS OF ADULT TREES OF CRIOLLO COCOA CULTIVARS (THEOBROMA CACAOL.) FROM A GERMPLASM BANK IN VENEZUELA

Abstract: We studied physiological traits of 12 Criollo cocoa cultivars growing in a germplasm bank in the southern region of Maracaibo Lake Basin, during the rainy (RS) and dry seasons (DS) of 2007. A further evaluation of photosynthetic responses to changes in environmental parameters was done on three cultivars: Los Caños 001 (LCA001), Sur Porcelana 010 (SP010) and Escalante 001 (ESC001) in 2009 and 2010. Leaf water potential ( L ) of most cultivars decreased during the DS of 2007, with the exception of ESC001. Maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
39
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 36 publications
(61 reference statements)
19
39
1
13
Order By: Relevance
“…Water status. High values of Ψ early in the morning were in agreement to those reported for young plants in well-watered conditions in an agroforestry system (Jaimez et al 2008;Tezara et al 2009;Araque et al 2012) and in young trees in a germplasm bank (Pereyra 2007;Ávila-Lovera et al 2016). By the time of the study (November and January) when monthly rainfall average was high, Ψ at noon of these trees indicated a low transpiration rate which may well be the result of an environment of low evaporative demand.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Water status. High values of Ψ early in the morning were in agreement to those reported for young plants in well-watered conditions in an agroforestry system (Jaimez et al 2008;Tezara et al 2009;Araque et al 2012) and in young trees in a germplasm bank (Pereyra 2007;Ávila-Lovera et al 2016). By the time of the study (November and January) when monthly rainfall average was high, Ψ at noon of these trees indicated a low transpiration rate which may well be the result of an environment of low evaporative demand.…”
Section: Discussionsupporting
confidence: 88%
“…The very low average A observed for both cultivars might be associated with low g s . Similarly, A values have been found to range from 0.7 to 6.5 µmol m -2 s -1 with low g s (20 -150 mmol m -2 s -1 ) in different studies Daymond et al 2011;Araque et al 2012;de Almeida et al 2014;Ávila-Lovera et al 2016). Higher instantaneous A and lower E determine a significant higher WUE in Criollo compared to Forastero, suggesting that Criollo cocoa could grow well in regions with limited water availability.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This may be due to environmental effects. Indeed, the environment may have played a role in the expression of some compatibility genes or traits [3,36]. The different levels of compatibility observed were a visible phenomenon indicated by the dropping of flowers, which could also be due to physiological traits and or environment conditions such as wind, rainfall, etc.…”
Section: Discussionmentioning
confidence: 99%
“…T. cacao is a heterozygous plant with a high variability for agronomic and quality traits [2,3]. Several studies have shown that the flowers of cocoa are androgynous and essentially fertilized by midges (Forcipomyia spp.)…”
Section: Introductionmentioning
confidence: 99%